Systemic Lupus Erythematosus with and without Anti-dsDNA Antibodies: Analysis from a Large Monocentric Cohort - Conti Fabrizio; Ceccarelli Fulvia; Perricone Carlo; Massaro Laura; Marocchi Elisa; Miranda Francesca; Spinelli Francesca Romana; Truglia Simona; Alessandri Cristiano; Valesini Guido (Mediators of Inflammation)
Objectives. The anti-dsDNA antibodies are a marker for Systemic Lupus Erythematosus (SLE) and 70–98% of patients test positive. We evaluated the demographic, clinical, laboratory, and therapeutical features of a monocentric SLE cohort according to the anti-dsDNA status. Methods. We identified three groups: anti-dsDNA + (persistent positivity); anti-dsDNA ± (initial positivity and subsequent negativity during disease course); anti-dsDNA − (persistent negativity). Disease activity was assessed by the European Consensus Lupus Activity Measurement (ECLAM). Results. We evaluated 393 patients (anti-dsDNA +: 62.3%; anti-dsDNA ±: 13.3%; anti-dsDNA −: 24.4%). The renal involvement was significantly more frequent in anti-dsDNA + (30.2%), compared with anti-dsDNA ± and anti-dsDNA − (21.1% and 18.7%, resp.; P=0.001). Serositis resulted significantly more frequent in anti-dsDNA − (82.3%) compared to anti-dsDNA + and anti-dsDNA ± (20.8% and 13.4%, resp.; P<0.0001). The reduction of C4 serum levels was identified significantly more frequently in anti-dsDNA + and anti-dsDNA ± (40.0% and 44.2%, resp.) compared with anti-dsDNA − (21.8%, P=0.005). We did not identify significant differences in the mean ECLAM values before and after modification of anti-dsDNA status (P=0.7). Conclusion. Anti-dsDNA status influences the clinical and immunological features of SLE patients. Nonetheless, it does not appear to affect disease activity.